Leveraging earth observation for monitoring, evaluation and learning of development programmes - Gouhari, Saeeda (Jameel Observatory for Food Security Early Action, 2025)
Presented at the Jameel Observatory Community of Practice meeting and drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 13-16 May 2025